Risk factors of cerebral palsy in the perinatal period - Santi Gunarwati; S. Yudha Patria; Madarina Julia (Paediatrica Indonesiana, 2008)
Background Cerebral palsy is an irreversible yet preventablecondition, thus it is necessary to know the risk factors of thedisease. The potential risk factors that are found in the perinataland neonatal period i.e. asphyxia, sepsis, very low birth weight,premature birth, and neonatal seizure. No available data for therisk factors of cerebral palsy in Indonesia.Objective To identify the perinatal risk factors in cerebral palsy.Methods We performed an age and sex-matched nested case-control study. The case group was children with cerebral palsywho were born at Sardjito Hospital during 1997-2005. The controlgroup was selected from the same population as the case group.Risk factors during the perinatal period consisted of asphyxia,sepsis, very low birth weight, premature birth and neonatal seizure.Logistic regression was used to determine the association betweenrisk factors and cerebral palsy.Results Univariate analysis showed that the following factors wererisk factors for cerebral palsy, i.e., asphyxia (OR 5.6, 95%CI 2.48;12.53); premature birth (OR 4.5; 95%CI 1.55; 13.13); and neona-tal seizure (OR 7.5, 95%CI 3.13; 18.03). On multivariate analysisrisk factors associated with cerebral palsy were asphyxia (aOR6.3, 95%CI 2.42; 16.66) and neonatal seizure (aOR 10.9,95%CI4.03; 29.97).Conclusion Asphyxia and neonatal seizure are significant riskfactors of cerebral palsy in perinatal period